FAKTOR-FAKTOR YANG MEMPENGARUHI INTENTION TO USE GUNA MENINGKATAN PANGSA PASAR LAYANAN VIDEO STREAMING - SYALOMIA, NAFTALI; SUTRISNO, NUNO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this study was to determine the effect of Perceived Ease of Use, Perceived Usefulness, Ritualized use and Instrumental Use toward Intention to Use on Netflix users in DKI Jakarta. This research used research method through a survey. Data analysis was carried out quantitatively and used a causal research design. Sample collected using Non-Probability Sampling with purposive sampling technique. The total sample used in this study was 147 respondents and will be processed using SPSS 25 software. The data analysis technique used in this study is multiple linear regression. The results of this study has shown that Perceived Ease of Use, Perceived Usefulness, Ritualized use and Instrumental Use have an influence on Intention to Use. This research is expected to provide input or suggestions to video streaming service companies, especially Netflix, which is the object of this research, is to be able to increasing the market share of video streaming companies in Indonesia.